A SPONGE (Stylissa sp.) ANTIOXIDANT TEST COLLECTED FROM MANADO BAY: UJI AKTIVITAS ANTIOKSIDAN (Stylissa sp.) YANG DIPEROLEH DARI TELUK MANADO - Billy Arthur Porajow; Adithya Yudistira; Erladys Rumondor (PHARMACON, 2023)
The Stylissa sp. were under the sea, and these sponge contains active compound, wich are more active than the compounds produced by teresterial plants. The purpose of this study was intended to test the antioxidant activity of the stylissa sp. Sample of the stylissa sp sponge was from the territorial of manado bay. This research an experimental laboratory by testing the ethanol extract of Stylissa sp sponge using DPPH method (1.1-diphenil-2- pikrhydrazil) to analyze antioxidant activity using spectrophotometri uv-vis with variations in concentrations 2, 4, 6, 8, and 10mg/ L. Was extracted Stylissa sp, sponge by maceration using ethanol 95% as a solvent. The value results of % inhibisi (2mg/ L); 86.50% (4mg/ L); 90.5% (6mg/L); 90.53% (8mg/ L) and 90,83% (10mg/L). The highest antioxidant activity at 10mg/L concentration with mean precentage 90.83% inhibisi. The result for this study indicate that the extract from ethanol Stylissa sp sponge has highest antioxidant activity. Keywords: Antioxidant, DPPH, Stylissa sp., bay of Manado